Effects of solvent extraction system on antioxidant activity of Lamium purpureum L. - Grujić, Slavica M.; Džamić, Ana M.; Mitić, Violeta D.; Stankov-Jovanović, Vesna; Marin, Petar D.; Stojanović, Gordana S. (HEMIJSKA INDUSTRIJA : : ХЕМИЈСКА ИНДУСТРИЈА, 2017)
Antioxidant and free radical scavenging activity of methanol, ethanol, ethyl acetate and chloroform extracts of aerial parts of Lamium purpureum L. was determined by DPPH, ABTS,FRAP and TRP assays. Contents of flavonoids and phenols were also investigated. The total phenolic content in the extracts, determined using Folin–Ciocalteu assay, ranged between 8.57 to 128.00 mg GAE/g d.e. while concentrations of flavonoids in the extracts varied from 24.20 to 39.80 mg QuE/g d.e. The highest phenolic content was found in methanol extract (128.00 mg GAE/g d.e.). The highest content of total flavonoids was identified in the methanol extract (39.80 mg QuE/g d.e.) and the lowest was in the chloroform (24.30 mg QuE/g d.e.). DPPH scavenging of the extracts was determined and obtained IC50 values ranged from 0.12 to 3.12 mg/mL of solution. The values of ABTS radical scavenging activity ranged from 0.35 to 1.80 mg AA/g. The highest ABTS antiradical activity was registered for methanol extract. The FRAP value was found within the range 0.08 to 1.04 µmol Fe/mg. The best radical scavenger was methanol (1.04 µmol Fe/mg). In reducing power assay different extracts of L. purpureum showed increasing of activity with increased concentration, and all extracts possessed substantial dose dependent antioxidant activity. The best reducing capacity was obtained with methanol extract of L. purpureum (0.0132 mg AA/mL). The results in this study confirmed that L. purpureum possesses moderate antioxidant properties.